Bacteria and the growing threat of multidrug resistance for invasive cardiac interventions - Grant N. Pierce; Craig Resch; Muntahi Mourin; Pavel Dibrov; Elena Dibrov; Amir Ravandi (Reviews in Cardiovascular Medicine, 2022)
Invasive cardiovascular procedures which include heart transplantations, congenital heart surgery, coronary artery bypass grafts, cardiac valve repair and replacement, and interventional cardiac electrophysiology procedures represent common mechanisms to treat a variety of cardiovascular diseases across the globe. The majority of these invasive approaches employ antibiotics as a regular and obligatory feature of the invasive procedure. Although the growing incidence of bacterial resistance to currently used antibiotics threatens to curtail the use of all interventional surgical techniques, it remains an underappreciated threat within the arsenal of cardiovascular therapies. It is reasonable to expect that the continued overuse of antibiotics and the frequent management of coronavirus disease 2019 (COVID-19) infected patients with high doses of antibiotics will inevitably accentuate the rise of multidrug resistance. The purpose of this article is to heighten awareness of the role of bacterial infections in cardiovascular disease, the use of antibiotics in today’s cardiovascular surgical theaters, the threat facing cardiovascular surgery should multidrug resistance continue to rise unabated, and the development of new antibiotic platforms to solve this problem.